Consequences of ADHD Medication Use for Children's Outcomes - Søren Dalsgaard; Helena Skyt Nielsen; Marianne Simonsen (Institute for the Study of Labor (IZA), 2014)
This paper estimates effects of early ADHD medication use on key human capital outcomes for children diagnosed with ADHD while using rarely available register based data on diagnoses and prescription drug purchases. Our main identification strategy exploits plausible exogenous assignment of children to hospitals with specialist physicians, while our analysis of health outcomes also allows for an individual level panel data strategy. We find that the behavior of specialist physicians varies considerably across hospitals and that the prescribing behavior does affect the probability that a given child is treated. Results show that children diagnosed with ADHD in pharmacological treatment have fewer hospital contacts if treated and that treatment to some extent protects against criminal behavior.
Keywords: I11; I12; 330; treatment; Attention Deficit/Hyperactivity Disorder; hospital variation; health; crime